DEVELOPMENT OF EDUCATIONAL COMIC "ACCOUNTING DAYS" AS ACCOUNTING LEARNING MEDIA TO IMPROVE STUDENTS LEARNING MOTIVATION - Isfanda Devi Maharani Fijri (Jurnal Pendidikan Akuntansi Indonesia, 2018)
This research aims to: 1) develop educational comic “Accounting Days” as accounting learning media, 2) know the feasibility of educational comic “Accounting Days” as accounting learning media, and 3) examine the improvement of students learning motivation of class XII Social after the development of educational comic “Accounting Days”. The research was conducted using Four-D model which consists of define, design, develop, and disseminate. The data collection technique was observation, interview, and questionnaires. Based on the analysis of students learning motivation average score, there is an increase in Students Learning Motivation’s average score from 3,21 to 3,40. However, the result of paired sample T test analysis shows that there is not any significant change in Students Learning Motivation after using Educational Comic “Accounting Days”. Thus, Educational Comic “Accounting Days” as Accounting Learning Media is not proven to improve Students’ Learning Motivation of class XII Social SMA Negeri 5 Yogyakarta Academic Year of 2017/2018. Keyword: Learning Media, Accountng, Educational Comic, Learning Motivation